An overview on AISI 304 stainless steel treated with aqueous soluted nitriding process. (2020) - Vaijayanth, Sheri; Koppula, Shivani; Subbiah, Ram; Sateesh, N.
Abstract: An examination is made on the arrangement treatment subsequent to nitriding (STAN) was performed to improve the weakness quality in type 304 steel by methods for the strong arrangement of nitrogen and the development of oxides on a business chromia-shaping compound (austenitic tempered steel AISI 304), in air at 900 °C. In research facility air, the weakness quality of the STAN example expanded contrasted with that of the untreated example yet was lower than that of the nitrided example. Then again, in 3% NaCl arrangement, the weakness quality of the untreated example was practically like the outcome in lab air, while the exhaustion qualities of the nitrided and the STAN examples diminished altogether contrasted with those in research center air. After the nitridation treatment played out, a γN strong arrangement is seen with no nitride development in the compound surface. Scanning electron microscope has been utilized to follow oxides advancement at the testing temperature. On account of untreated examples, four oxides are watched all through the oxidation test. Our outcomes show that nitridation expanded the high temperature oxidation opposition of the 304 hardened steel at900°C.